SEMIOTIK DALAM TATARAN SEMANTIK (SEMIOTICS INTERPRETING MEANING) - Zainuddin Zainuddin (BAHAS, 2021)
This article deals with semiotics and semantics. In other words, this article discussing about semiotics Interpreting meaning. Semiotics as the linguistic sain concerning the two important aspects which cannot be seperated, namely the signfied and signifier, since each have different meaning to be considered. De Saussure called the concept “signfie’,” (meaning) “signifiant”, or “signifier” (form). These two sides are so intimately related that they can be compared to a piece of paper. Since it is impossible to cut one sides of the paper without cutting the other. This concept can be interpreted that meaning (signified) is realized  in form (signifier) as semiotics of language expression. It means that semiotics of language consis of 3 components namely, meaning, form and expression. Where is meaning as semiotic sign and form as lexicogrammar, an expression refers to phonology, graphology, of sign. Keywords : Semiotics, Meaning